Benzene coadsorbed with CO and NO on Ru(001). I. A UPS study with synchrotron radiation - Heimann, P.A.; Jakob, P.; Pache, T.; Steinrück, Hans-Peter; Menzel, Dietrich (Surface Science, 1989)
Angle-resolved UPS spectra were taken of the coadsorbate systems ( 13 × 13)R13.9° CO+ benzene and (3 × 3) NO+ benzene, on Ru(001). The component molecules were also studied as pure layers. From symmetry selection rules, the benzene molecule is shown to lie parallel to the surface and to retain six-fold symmetry for saturated benzene as well as for both coadsorbed layers. When coadsorbed with benzene, NO is present only in bridge sites. Comparing the pure and coadsorbed layers, the binding energies are different: the coadsorbed benzene orbitals shift to lower values and the CO and NO orbitals shift to higher values. These energy shifts are interpreted as a purely electrostatic initial-state change in the case of CO+ benzene. For NO+ benzene, it is suggested that this electrostatic effect is accompanied by some change in bonding. © 1989.